The use of pictures and videos showing dermal and mucosal symptoms by patients in medical practice - Pekar, Joanna; Skolarczyk, Justyna; Pekar, Piotr; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2018)
Introduction. Diagnostic imaging is an extremely important step towards making the final diagnosis of many diseases. Among the criteria of numerous diseases are cutaneous or mucosal changes, which occur paroxysmal and persist for a short time. Currently, patients are increasingly using technological progress and they document such changes with the help of mobile phone cameras. Purpose of work. The aim of the study was to determine whether patients turn to doctors with photographs or videos documenting their symptoms and whether it is useful in making the final diagnosis. Material and methods. The research method was a questionnaire constructed by authors of the article, which was answered by 107 doctors employees of the Medical University of Lublin and the Medical University of Bialystok. Participation in the study was voluntary and anonymous. Results. 75 (70%) of the respondents admitted that the patients brought them photos and videos documenting their symptoms. 73 (68%) of respondents considered them useful in making final diagnosis of diseases. Pictures and videos of head were shown to the doctors by 39 (36%) patients, pictures of neck by 30 (28%), pictures of upper limb by 37 (34%), pictures of lower limb by 39 (36%), pictures of chest by 38 (35%), pictures of stomach by 26 (24%) patients , pictures of pelvis by 26 (24%) patients, pictures of the back by 12 (11%), pictures of nails by 7 (6.5%), pictures of hair by 5 (4.6%) and pictures of eyes by 7 (6.5%) patients. Conclusions. Documenting short lasting dermal and mucosal symptoms by patients in the form of self photographs or films is a new tool that can help doctors in finding the right diagnosis.